Following radical pair reactions in solution: a step change in sensitivity using cavity ring-down detection - Maeda, K; Neil, S; Henbest, K; Weber, S; Schleicher, E; Hore, P; Mackenzie, S; Timmel, C (American Chemical Society, 2011)
The study of radical pair intermediates in biological systems has been hampered by the low sensitivity of the optical techniques usually employed to investigate these highly reactive species. Understanding the physical principles governing the spin-selective and magneto-sensitive yields and kinetics of their reactions is essential in identifying the mechanism governing bird migration, and might have significance in the discussion of potential health hazards of electromagnetic radiation. Here, we demonstrate the powerful capabilities of optical cavity-enhanced techniques, such as cavity ring-down spectroscopy (CRDS) in monitoring radical recombination reactions and associated magnetic field effects (MFEs). These include submicrosecond time-resolution, high sensitivity (baseline noise on the order of 10–6 absorbance units) and small (μL) sample volumes. Combined, we show that these represent significant advantages over the single-pass flash-photolysis techniques conventionally applied. The studies described here focus on photoinduced radical pair reactions involving the protein lysozyme and one of two possible photosensitizers: anthraquinone-2,6-disulphonate and flavin mononucleotide. CRDS-measured MFEs are observed in pump-probe experiments and discussed in terms of the sensitivity gains and sample-volume minimization afforded by CRDS when compared with flash photolysis methods. Finally, CRDS is applied to an in vitro MFE study of intramolecular electron transfer in the DNA-repair enzyme, Escherichia coli photolyase, a protein closely related to cryptochrome which has been proposed to mediate animal magnetoreception.